SYED MUHAMMAD NAQUIB AL ATTAS'S PHILOSOPHY OF EDUCATION: A PERENNIALIST CRITICISM OF THE SECULARIZATION OF EDUCATION - Anugrah Giffari; Hironimus Dafa; Ishomuddin (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2025)
This article investigates the perennialist philosophical critique by Syed Muhammad  Naquib Al-Attas of the secularization of education, which is identified as the source  of the modern educational crisis, a crisis marked by pragmatism and the erosion of  values. This research analyzes Al-Attas's body of work to unveil his critique. The  findings show that Al-Attas perceives secularization not just as a political process,  but rather as a philosophical program that leads to the desacralization of nature  and the despiritualization of man. The most damaging consequence in education is  the "loss of adab," defined as the failure to acknowledge the hierarchy of reality  and knowledge, resulting in epistemological and ethical chaos. To solve this, Al Attas offers the project of the "Islamization of Contemporary Knowledge." Its  objective is to re-embed knowledge within the Islamic worldview (ru’yat al-Isl?m li  al-wuj?d), aspiring to cultivate the "Man of Adab" (al-ins?n al-adab?). The  implication of this study advocates for a fundamental reconstruction of Islamic  educational curricula that prioritizes the inculcation of adab over mere technical  competence, thereby offering a strategic counter-narrative to global pragmatism.  This article concludes that Al-Attas's philosophy offers a strong theoretical  framework to diagnose the crisis in education and to propose a restorative solution  that is rooted in the Islamic intellectual tradition and consistent with the principles  of perennial universalism.